A Case Report of Parry–Romberg Syndrome Misdiagnosed as Multiple Sclerosis - Long, Ling; Kang, Zhuang; Chen, Shaoqiong; Cui, Chunping; Men, Xuejiao; Qiu, Wei (Frontiers in Neurology, 2020)
Background: Parry–Romberg syndrome (PRS) is a rare disease that causes hemiatrophy of the face. The pathophysiological mechanisms involved in its etiology are unknown, but several previous reports suggest the involvement of autoimmune factors. Herein we describe the case of a patient with PRS who was initially misdiagnosed as having multiple sclerosis (MS). Relevant literature is briefly reviewed, and some previous reports suggesting associations between PRS and autoimmunity are discussed. Case presentation: A 34-year-old man presented with recurrent paroxysmal weakness of the right hand, a 3-year history of unilateral tinnitus, and headache for 6 months. MS was initially diagnosed but he was subsequently diagnosed as having PRS on the basis of clinical manifestations and radiological findings. Conclusions: PRS may be associated with an autoimmune pathogenesis, but the present case does not support that theory.